2016
DOI: 10.1021/acs.jchemed.5b00818
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Cobalt(II) Cage: An Undergraduate Laboratory Experiment That Produces a ParaSHIFT Agent for Magnetic Resonance Spectroscopy

Abstract: Laboratory experiments that demonstrate the effect of paramagnetic complexes on chemical shifts and relaxation times of protons are a useful way to introduce magnetic resonance spectroscopy (MRS) probes or magnetic resonance imaging (MRI) contrast agents. In this undergraduate inorganic chemistry experiment, a paramagnetic Co­(II) cage complex is prepared by reduction of a classical Co­(III) cage complex. The Co­(II) cage behaves as a paramagnetic shift agent (paraSHIFT) and produces relatively sharp and highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…CEST spectra,, plotted as the percent decrease in water proton magnetization as a function of presaturation pulse frequency were recorded for [Ni( L5 )] 2+ , [Ni( L2 )] 2+ , and [Ni( L3 )] 2+ (Figure , Figure S18 and Figure S19). No CEST effect could be detected for [Ni( L1 )] 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…CEST spectra,, plotted as the percent decrease in water proton magnetization as a function of presaturation pulse frequency were recorded for [Ni( L5 )] 2+ , [Ni( L2 )] 2+ , and [Ni( L3 )] 2+ (Figure , Figure S18 and Figure S19). No CEST effect could be detected for [Ni( L1 )] 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Co­(II) paraCEST agents reported to date typically are encapsulated by a macrocyclic ligand and have exchangeable amide NH, alcohol OH, or heterocyclic NH protons. , There are no examples of exchangeable water ligands on Co­(II) complexes that produce CEST peaks, to the best of our knowledge. In contrast, Ln­(III) paraCEST agents frequently have a slowly exchanging water ligand that gives rise to a CEST peak .…”
Section: Introductionmentioning
confidence: 98%
“…In the present work, the temperature dependence of paramagnetic chemical shifts of complex [Co(DTPA)] 3is studied and the prospects of its use as an NMR thermal sensor for local temperature measurements are estimated. of CSs is about 1.3 ppm/K [19]; a close value (1.38 ppm/K) was also obtained for complex [Co(diNOSar)]Cl 3 [4]. The authors of [20] reported an unprecedented value of 15 ppm/K for the hydride proton in complex t-Bu (PNP) with iron, even though this complex cannot be currently considered as a temperature-sensitive MRI probe.…”
Section: Introductionmentioning
confidence: 69%
“…The stronger the temperature dependence of the chemical shift, the more accurately the temperature can be determined by analyzing the signal's position. Based on this principle, a number of MRI procedures have been developed for the diagnosis of inflammation and oncological diseases [2][3][4][5]. Complexes of transition 3d-block elements with polyaminopolycarboxylates (such as EDTA, DTPA, DOTA) have been considered as the most promising materials for such applications.…”
Section: Introductionmentioning
confidence: 99%